1992
DOI: 10.1111/j.1532-5415.1992.tb02101.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cognitive, Psychiatric, and Behavioral Disturbances in Patients with Dementia: The Neurobehavioral Rating Scale

Abstract: The NRS is a useful instrument for structured assessment of a broad range of cognitive, psychiatric, and behavioral disturbances in patients with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
3
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(71 citation statements)
references
References 33 publications
5
62
3
1
Order By: Relevance
“…Verhey et al (1993), from a series of 170 cases of dementia (103 with AD), also found that impaired insight correlated significantly with GDS scores. The finding of a difference between two groups of AD cases of differing severity may depend on the range of cases selected: Sultzer et al (1992) classified AD cases according to MiniMental State score (MMSE, Folstein et al, 1975) and reported that more severe (MMSE < 10) AD cases had significantly worse insight than less severe (MMSE >lo) cases. Reed et al (1993) and Michon et al (1994) used less severe patient groups (MMSE >12 and MMSE >lo,respectively) and, perhaps as a consequence, found no significant relationship between severity and insight.…”
Section: Severity Of Dementia and Awarenessmentioning
confidence: 98%
“…Verhey et al (1993), from a series of 170 cases of dementia (103 with AD), also found that impaired insight correlated significantly with GDS scores. The finding of a difference between two groups of AD cases of differing severity may depend on the range of cases selected: Sultzer et al (1992) classified AD cases according to MiniMental State score (MMSE, Folstein et al, 1975) and reported that more severe (MMSE < 10) AD cases had significantly worse insight than less severe (MMSE >lo) cases. Reed et al (1993) and Michon et al (1994) used less severe patient groups (MMSE >12 and MMSE >lo,respectively) and, perhaps as a consequence, found no significant relationship between severity and insight.…”
Section: Severity Of Dementia and Awarenessmentioning
confidence: 98%
“…Characteristic symptoms in patients with AD are listed in table 1. Delusions occur in approximately 30-40% of patients with AD [7][8][9], fluctuate over time but often persist [10,11], and are associated with aggressive behavior [12][13][14][15] and rapid cognitive decline [9]. Hallucinations occur in approximately 5-20% of patients with AD [8,10,16,17], although the proportion varies considerably across studies.…”
Section: Psychosis In Admentioning
confidence: 99%
“…[24][25][26][27][28][29][30] For example, depression rating instruments that measure a greater number of somatic items achieve higher depression rates in more demented patients, whereas instruments assessing subjective complaints pick up less information in this group. 31 In the most severely demented, caregiver information is generally more likely to identify depression than self-report. 23 Very subtle depressive symptoms, such as reduction of motivation and interest may present before the clinical diagnosis of dementia is made.…”
Section: Depressive Symptomsmentioning
confidence: 99%